Health education – local solutions, global challenges. Good practice examples in English schools - Leek, Joanna (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
The paper presents health education, focusing on good practice examples in English schools. The first part contains a review of the education system in England, and basic principles of core curriculum of general education. It contains a description of concepts of health education in England with indications to core curricula of primary and secondary schools in the field of health education. The second part contains an overview of educational initiatives in Europe in the field of health education.